Microbiological quality analysis of fresh vended fruit juices and water sold in roadside stalls in Dhaka Metropolis by MPN method (Stamford Journal of Microbiology, 2017)
Quality of drinking water and juice is very important because if the quality deteriorates by the contamination of faecally originated microorganisms, it may cause serious diarrhea associated problems leading to death. In overpopulated countries like Bangladesh, this is a common scenario to experience diarrheal diseases due to drinking non-potable water as well as contaminated fresh juices. Present study was conducted to determine the quality of drinking water and juice by detection of indicator bacteria Escherichia coli by MPN (Most Probable Number) method which was performed by three consecutive steps including presumptive test, confirmed test and completed test. Other gram negative bacteria were also identified by biochemical methods. The indicator bacterium Escherichia coli was detected in two water samples out of 15 samples and one juice sample out of fifteen samples respectively during the MPN test method. Other Gram negative bacteria found in both water and juice samples included Klebsiella spp., Alcaligenes spp., Pseudomonas spp. and Proteus spp. The quality of drinking water and juice was found to be good in Bangladesh but proper hygiene should be maintained more strictly to avoid the contamination by other gram negative bacteria which are also capable of causing disease.Stamford Journal of Microbiology, Vol.7(1) 2017: 1-6